2018
DOI: 10.1007/s00592-017-1098-3
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of resveratrol on markers of oxidative stress in patients with type 2 diabetes: a randomized, double-blind, placebo-controlled clinical trial

Abstract: Our study demonstrated that 8 weeks of supplementation with 800 mg/day resveratrol has an antioxidant effect in the blood and PBMCs of patients with T2D. Clinical Trial Registry number and website IRCT registration number: IRCT2015072523336N1 and http://en.search.irct.ir/view/24752 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
96
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 48 publications
5
96
1
3
Order By: Relevance
“…Several trials have aimed to investigate the antiobesity effects of resveratrol in human. Contrary to our findings, some trials revealed significant effects of resveratrol supplementation on anthropometric measures in patients with T2DM (Imamura et al, 2017;Kumar & Joghee, 2013;Seyyedebrahimi, Khodabandehloo, Esfahani, & Meshkani, 2018). However, one study reached null results (Bo et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…Several trials have aimed to investigate the antiobesity effects of resveratrol in human. Contrary to our findings, some trials revealed significant effects of resveratrol supplementation on anthropometric measures in patients with T2DM (Imamura et al, 2017;Kumar & Joghee, 2013;Seyyedebrahimi, Khodabandehloo, Esfahani, & Meshkani, 2018). However, one study reached null results (Bo et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…The results of two studies on mice indicated that oral administration of 20 mg/kg/d of RSV for 2 weeks downregulated the expression of RAGE . However, two human studies showed inconsistent results for the effects of RSV on glycation reactions and expression of RAGE . Roggerio et al demonstrated that receiving 500 mg/day of RSV for 30 days decreased the gene expression but not the serum concentration of RAGE .…”
Section: Resultsmentioning
confidence: 99%
“…Roggerio et al demonstrated that receiving 500 mg/day of RSV for 30 days decreased the gene expression but not the serum concentration of RAGE . Seyyedebrahimi et al also found that oral supplementation of 800 mg/day RSV for 2 months considerably decreased plasma protein carbonyl content in the patients with DM while the expression of RAGE and Nrf 2 have not been affected …”
Section: Resultsmentioning
confidence: 99%
“…To avoid cellular damage by ROS, hepatocytes neutralize the harmful effects of ROS by activating the antioxidant enzymes such as heme oxygenase 1 ( HO1 ), NAD(P)H:Quinone Oxidoreductase 1 ( NQO1 ), and manganese superoxide dismutase ( Mn‐SOD ). Importantly, many of these antioxidant enzymes are encoded by genes that are regulated by transcription factor nuclear factor‐erythroid 2‐related factor 2 (Nrf2) . In this regard, it has been demonstrated that Nrf2 protects hepatocytes against oxidative damage through its important function in the prevention of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, many of these antioxidant enzymes are encoded by genes that are regulated by transcription factor nuclear factor-erythroid 2-related factor 2 (Nrf2). 9,10 In this regard, it has been demonstrated that Nrf2 protects hepatocytes against oxidative damage through its important function in the prevention of oxidative stress. Besides the activation of the genes involved in the elimination of ROS derived from lipid peroxidation, the protective role of Nrf2 in NAFLD is also mediated through negative regulation of genes that promote hepatic lipid deposition.…”
Section: Introductionmentioning
confidence: 99%